A novel use for Levey-Jennings charts in prenatal molecular diagnosis - Binghuan Weng; Ya-li Xu; Jun Ying; Hao-kun Yang; Lan Su; Yan-mei Yang; Min Chen (BMC, 2020)
Abstract Background The goal of this study was to determine whether Levey-Jennings charts, which are widely used in clinical laboratories, can be used to create standardized internal quality controls (IQCs) for prenatal molecular diagnosis. Methods Aneuploid amniocyte lines with trisomy 13, 21, and 18, and 47,XXY were established by transfection with SV40LTag-pcDNA3.1(−)and combined at different ratios to generate aneuploidy chimeric quality-control cell mixtures A to H. These quality-control cells were then used to calculate the X ¯ $$ \overline{X} $$ , X ¯ $$ \overline{X} $$ ±1 standard deviation (SD), X ¯ $$ \overline{X} $$ ±2 SD, and X ¯ $$ \overline{X} $$ ±3 SD values to develop standardized IQCs for methods used for the prenatal diagnosis of aneuploidies such as FISH. Results Methods for constructing aneuploid amniocyte lines were developed and a set of quality-control cells (A-H) were prepared. The X ¯ $$ \overline{X} $$ ±1 SD, X ¯ $$ \overline{X} $$ ±2 SD, and X ¯ $$ \overline{X} $$ ±3 SD values of these quality-control cells for trisomy 13 and 21 were 10.2 ± 1.7, 10.2 ± 3.4, and 10.2 ± 5.1, and 90.3 ± 2.3, 90.3 ± 4.6, and 90.3 ± 6.9, respectively. Based on the values and Levey-Jennings charts, a set of standardized IQCs for prenatal diagnosis such as FISH were established. Conclusions This method resolves the problems of a shortage of quality-control materials and a lack of quality-control charts in prenatal molecular diagnosis such as NIPT, NGS, aCGH/SNP, PCR, and FISH. Levey-Jennings chart-based IQCs for prenatal diagnosis such as FISH can be used to easily monitor whether IQC results are within acceptable limits, and then infer whether the diagnostic results for clinical samples are reliable. We expect that this standardized IQC will be useful for a wide range of molecular diagnostic laboratories.